Using STEM Development Worksheets at Free Fall Montion Concept to Toward the Generic Science Skills - Didik Setiawan; Supriyadi Supriyadi; Ellianawati Ellianawati (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze about the eligible, characteristics, and skill upgrade generic science for students at STEM (Science, Technology, Engineering, and Mathematics) worksheets. Evaluating student responses at STEM learning worksheets. This research is adopted by ADDIE method. It is consisting into of five stages such as analysis, design, development, implementation and evaluation. The results of study show percentage 87.80% excelent category at feasibility test. Second, the main characteristic of development student worksheet is based on STEM (Science, Technology, Engineering, and Mathematics) based learning to improve science generic skills. Third, the result of study is in science generic skills at MA Nurus Sunnah Semarang the average percentage is 80% good category with small-scale and large-scale is at Al Fattah Terboyo High School Semarang the average percentage is 85.35% excelent category at skill upgrade, it is used by students of class X MIPA SMA/MA as a supporting learning resource in the learning process. Based on text above, it can be conclude that the student are able to understand about the learning as well